2021
DOI: 10.3390/ijerph18031101
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Importance of Cost of Illness Analysis in Rare Diseases: A Proposal

Abstract: In the field of rare diseases (RDs), the evidence standard is often lower than that required by health technology assessment (HTA) and payer authorities. In this commentary, we propose that appropriate economic evaluation for rare disease treatments should be initially informed by cost-of-illness (COI) studies conducted using a societal perspective. Such an approach contributes to improving countries’ understanding of RDs in their entirety as societal and not merely clinical, or product-specific issues. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…As mentioned earlier, the BURQoL-RD project in Europe used a similar approach regarding the costs taken into consideration but was limited to 10 rare diseases ( López-Bastida et al, 2016a ), while García-Pérez et al ( García-Pérez et al, 2021 ) report some diversity in the costs included in the studies they reviewed, all of them including direct medical costs in their analysis but only 60, 69 and 43% including respectively non-medical costs, loss of productivity and costs of informal care. As Angelis et al ( Angelis et al, 2015 ) and Armeni et al ( Armeni et al, 2021 ) point, there exists significant heterogeneity in the identification of costs associated with rare diseases, as well as in the methodologies used to do so. This in turn complicates comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, the BURQoL-RD project in Europe used a similar approach regarding the costs taken into consideration but was limited to 10 rare diseases ( López-Bastida et al, 2016a ), while García-Pérez et al ( García-Pérez et al, 2021 ) report some diversity in the costs included in the studies they reviewed, all of them including direct medical costs in their analysis but only 60, 69 and 43% including respectively non-medical costs, loss of productivity and costs of informal care. As Angelis et al ( Angelis et al, 2015 ) and Armeni et al ( Armeni et al, 2021 ) point, there exists significant heterogeneity in the identification of costs associated with rare diseases, as well as in the methodologies used to do so. This in turn complicates comparison between studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, this could be explained by the selection of 10 diseases included in the BURQoL-RD project ( López-Bastida et al, 2016a ), which used a Delphi approach combined with a Caroll Diagram to select a representative set of rare diseases based on three criteria: prevalence, availability of effective treatment and need for care. The availability of COI studies being positively correlated to the existence of a treatment ( Armeni et al, 2021 ) and knowing that 95% of rare diseases currently do not have a treatment available ( Sequeira et al, 2021 ), it could be argued that a vast majority of conditions are thus left outside the scope of COI and that there is a need to go beyond the existence of a treatment to conduct COI studies to illustrate the true impact of rare diseases. The paucity of available treatments further emphasises the importance of adopting a holistic approach when investigating the impact of rare diseases to avoid leaving out of scope conditions for which there are no medical options but for which daily impacts remain high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs of illness studies are important in defining healthcare and research priorities for governments and biopharmaceutical companies 16 . However, such studies in rare diseases, including EB, are scant 17 ,.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Costs of illness studies are important in defining healthcare and research priorities for governments and biopharmaceutical companies. 16 However, such studies in rare diseases, including EB, are scant. 17,18 A questionnaire-based study in 8 European countries in 2016 reported average annual care costs of €31,390 for all EB types.…”
mentioning
confidence: 99%